The Secret Path to Reconciliation: Impact and Legacy of Gord Downie’s Musical Activism - McCallum, Duncan (CAML Review / Revue de l'ACBM, 2024)
In 2016, Canadian musician Gord Downie released a solo concept album titled Secret Path, which dealt with the death of Chanie Wenjack, an Anishinaabe boy who passed away after escaping an Ontario residential school in the 1960s. This album came just one year after the Final Report of the Truth and Reconciliation Commission (TRC) was published, marking a major national step in the reconciliation process. This, in combination with Downie’s terminal brain cancer diagnosis that same year, gave the album a particularly heightened prominence within Canada. This paper examines Downie’s album through the musicological framework of secondary musical witnessing, where Downie acts as a witness in defining the story of Chanie Wenjack. Through analyzing Downie’s role as a musical witness, broader questions of Indigenous allyship are explored through the colonial lens of settler witnessing. This paper aims to explore the nuances and circumstances around Secret Path to understand its historical and cultural significance in the reconciliation movement upon its release, as well as the problems with its legacy related to Indigenous allyship when judged by modern standards as a way of demonstrating how far the reconciliation movement has progressed since 2016.